Інтелектуальний потенціал і читацькі інтереси вищого українського духовенства ранньомодерного часу: характеристика маловідомих джерел дослідження - Кагарлик, С. (Народна творчість та етнографія, 2008)
The high Ukrainian clergy’s intellectual potential and reader’s interests of the early-modern time: the characteristic of poor known sources for research. The poor known sources to research high Ukrainian clergy’s intellectual potential of the earlymodern time such as testaments, description of property of spiritual persons, book donations, exlibrises and other inscriptions in the books are characterized in this article. The meaning of historicalstatistic descriptions of eparchies (especially of Chernihiv, Kharkiv and Poltava), which contain rich information about possessive inscriptions on the old printed books of spiritual persons and illustrate their readability, are also shown there.